Implementation of building information modeling (BIM) in Pakistan construction industry - Bhatti, Imtiaz Ali; Abdullah, Abd Halid; Nagapan, Sasitharan; Bhatti, Nabi Bux; Sohu, Samiullah; Ahmed Jhatial, Ashfaque (Etasr, 2018)
This paper examines the implementation of building information modeling (BIM) in construction industry. Various initiatives and approaches are used in different countries to promote the BIM implementation in their construction industries. The real implementation and use of BIM remains a major concern of the construction industry. This study investigates the implantation of BIM globally, in developed countries and the percentage of implementation of BIM in constriction industry of Sindh, Pakistan. This research demonstrates 131 responses from BIM users regarding BIM implementation whose collaboration aspects produce the highest positive impact. The adopted methodology is an online questionnaire survey and literature review which was conducted to find out the implementation of BIM in construction industries of developed countries. This research reveals that BIM implementation is increasing continuously over the past few years. A Number of developed countries are emerging successful BIM implementation strategies, United States, United Kingdom, Germany, France are generally leading the way. However, according to our study findings, only 11% of industries have implemented BIM in Sindh, Pakistan.